Pengaruh Program Transformasi Perpustakaan Berbasis Inklusi Sosial Terhadap Kepuasan Masyarakat Taman Ilmu Nagari Koto Tinggi - Sanda, Luna Putri; Nabila, Jeihan (Scinary, 2024)
The purpose of this study is to describe the influence of the library transformation program based on social inclusion on community satisfaction at Taman Sains Nagari Koto Tinggi Kuranji. This research employs a descriptive quantitative method, with the population consisting of visitors to the Taman Sains Nagari Koto Tinggi library in Padang Pariaman Regency, and a sample of 100 people determined using the Slovin formula. The data collection technique utilized Simple Random Sampling. Data were analyzed using mandatory tests including normality test, correlation test, linearity test, t-test, and coefficient of determination test. Based on the results, it can be concluded that the social inclusion-based transformation program has an effect on community satisfaction at Taman Sains Nagari Koto Tinggi, with the hypothesis test showing a significance value of 0.000 (p<0.05), indicating that variable X (social inclusion) influences variable Y (community satisfaction).